Navorsingsmetodologie hoe om behoeftes in die gemeenskap te beraam - M. Poggenpoel (AOSIS, 1983)
An assessment of community needs is part of the scientific process used by the multi-professional health team to assess, plan, implement and evaluate a community health service. An accurate assessment of both perceived needs and those identified by health professionals is necessary for an effective service. Such an assessment requires the use of research methodology, including scientific research methods, techniques and instruments. There are also a number of essential questions to which answers must be found by the research to ensure a comprehensive assessment.